2006
DOI: 10.1079/pavsnnr20061018
|View full text |Cite
|
Sign up to set email alerts
|

Is sialic acid in milk food for the brain?

Abstract: The rapid brain growth of infants places exceptionally high demands on the supply of nutrients from the diet. Human milk is the best source of food for brain growth and cognition. One of nature's richest sources of sialic acid, a vital component of brain gangliosides and the building block of polysialic acid (PSA) on neural cell adhesion molecule (NCAM), is found in human breast milk. However, infant formulas contain very little amounts. Gangliosides and polysialylated NCAM in the brain have an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…Figure modified from Karim and Wang (1) with kind permission from CAB Reviews. Sia residues on gangliosides around the synaptic cleft are thought to modulate Ca 2+ levels via Ca 2+ -ganglioside interactions (1). During the resting potential, the presynaptic membrane is closed due to tight Ca 2+ -ganglioside associations with the aid of negative charges from terminally positioned Sia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure modified from Karim and Wang (1) with kind permission from CAB Reviews. Sia residues on gangliosides around the synaptic cleft are thought to modulate Ca 2+ levels via Ca 2+ -ganglioside interactions (1). During the resting potential, the presynaptic membrane is closed due to tight Ca 2+ -ganglioside associations with the aid of negative charges from terminally positioned Sia.…”
Section: Resultsmentioning
confidence: 99%
“…However, the synaptic connections between these neurons are in large part established and elaborated after birth. Important neurodevelopmental processes that occur throughout this critical period include synaptic networking, dendritic arborization, and cell multiplication and migration (1). In general, synapses are formed at a very rapid rate during the early months of life, usually achieving maximum density between 6 and 12 mo after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Though humans possess the requisite enzymes for endogenous Neu5Ac synthesis (54, 55), the rate-limiting enzyme (UDP-N-acetylglucosamine-2-epimerase (UDP-GlcNAc-2-epimerase)/N-acetylmannosamine kinase (ManNAc Kinase)) of this pathway has been shown to exist only at low levels in neonatal rats and guinea pigs (56). Researchers hypothesize that levels of ManNAc Kinase—and thus Neu5Ac synthesis potential—are low in human infants, especially those born prematurely (47, 57). Concurrently, the level of intestinal neuraminidase (which can release Neu5Ac from various glycans) has been shown to be highest in rats and mice during the suckling period (58).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the sialic acid from EBN was synthesized through the placenta and maternal milk which contributed to the neuronal transmission and synaptic plasticity development in their offspring (Oliveros et al., 2018; Wang et al., 2003; Xie et al., 2018). In addition, the synthesis of sialic acid in the F1 and F2 offspring improved the concentration of ganglioside bound and protein bound in the brain, suggesting that an increased sialylation on gangliosides mediates the learning and memory responses (Karim & Wang, 2006). In fact, the metabolism of sialic acid from EBN produced several neuraminic acids (e.g., N‐acetyl‐D‐galactosamine, N‐acetyl‐D‐glucosamine, and N‐acetylneuraminate) that are integral structural and functional components of the nervous system (Karim & Wang, 2006; Khalid et al., 2019; Yu‐Qin et al., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the synthesis of sialic acid in the F1 and F2 offspring improved the concentration of ganglioside bound and protein bound in the brain, suggesting that an increased sialylation on gangliosides mediates the learning and memory responses (Karim & Wang, 2006). In fact, the metabolism of sialic acid from EBN produced several neuraminic acids (e.g., N‐acetyl‐D‐galactosamine, N‐acetyl‐D‐glucosamine, and N‐acetylneuraminate) that are integral structural and functional components of the nervous system (Karim & Wang, 2006; Khalid et al., 2019; Yu‐Qin et al., 2000). Therefore, the ability of F1 and F2 mice to complete the Y‐maze learning task suggested that the intake of exogenetic sialic acid from EBN is an essential micronutrient for optimal brain metabolism and cognitive development in multigeneration mice.…”
Section: Discussionmentioning
confidence: 99%